2016
DOI: 10.1002/alr.21778
|View full text |Cite
|
Sign up to set email alerts
|

The extended nasoseptal flap for coverage of large cranial base defects

Abstract: The relaxing incision described here creates a flap that allows for reconstruction of a larger range of skull base defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
12
1
1
Order By: Relevance
“…In our cadaveric study without sphenoidotomy, the CPFS was ≤0.5 cm in 6 out of the 15 specimens (40%), unlike in some other studies that used Western cadavers and showed a lower rate of CPFS of ≤0.5 cm [ 7 , 9 ]. These findings suggested that the degree of coverage in our study was relatively lower, which may have been due to a significantly shorter length of the PNSF in our Korean specimens than in the specimens of other studies [ 17 ]. Another radioanatomic study in a Korean population reported a CPFS of ≤0.5 cm in 29% of the patients [ 8 ].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In our cadaveric study without sphenoidotomy, the CPFS was ≤0.5 cm in 6 out of the 15 specimens (40%), unlike in some other studies that used Western cadavers and showed a lower rate of CPFS of ≤0.5 cm [ 7 , 9 ]. These findings suggested that the degree of coverage in our study was relatively lower, which may have been due to a significantly shorter length of the PNSF in our Korean specimens than in the specimens of other studies [ 17 ]. Another radioanatomic study in a Korean population reported a CPFS of ≤0.5 cm in 29% of the patients [ 8 ].…”
Section: Discussioncontrasting
confidence: 51%
“…7 ). Second, multilayered reconstruction technique, pericranial flap, or several types of extended nasoseptal flaps can be solely applied to cover the large skull base defect [ 17 19 ]. Moreover, anteriorly based mucosal flaps, including anteriorly based inferior turbinate flap and anterior pedicle lateral nasal wall flap, can be added to cover the most anterior part of ASB, which cannot be covered by PNSF [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pedicled intranasal flaps, although ideal for the majority of anterior skull base surgery, may lack sufficient length or area for select defects that are far anterior/posterior or large in size. The extended NSF, which includes the floor of the nasal cavity and inferior meatus, has been shown to reach reconstruction of most clival defects up to the foramen magnum . However, the anterior frontal area adjacent to the posterior table of the frontal sinus remains challenging for endoscopic endonasal reconstruction with the NSF.…”
Section: Discussionmentioning
confidence: 99%
“…The standard NSF includes the majority of the septal mucosa and extends to the junction of the nasal floor and septum. Several modified techniques have been proposed to increase the surface area of the NSF, such as extending incisions to the nasal floor mucosa and the inferior meatus . The NSF may be limited, however, in its reach to the most anterior aspects of anterior cranial base defects or for full coverage of defects from transclival approaches to the posterior fossa …”
Section: Introductionmentioning
confidence: 99%
“…Although such studies confirm the utility of pedicled flaps for skull‐base reconstruction, resections continue to be more aggressive, demanding innovative reconstructive options. While the NSF is the workhorse for endoscopic skull‐base reconstruction, Bassett et al . report successful modification of this flap, using an extended NSF to improve its reach superiorly into the frontal sinus.…”
mentioning
confidence: 99%